Cash in the Pot of Gold A Critical Review on the Book “Saadi's Arabic Poetry Based on Applied Criticism” - Mohammadreza Najjarian; Nafise Raisi Mobarake (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The research in Saadi's Arabic poetry is not at par with the Persian poems of this famous Iranian poet, either in terms of quality or quantity, this is more obvious in the correction and description of the text of these poems. The book of review of “Saadi's Arabic Poems Based on Applied Criticism” was published for the first time in 2015 by Shahid Madani University of Azerbaijan publisher. Amir Muqaddam Mottaghi, the author of the book, has tried, in his research, to evaluate Saadi's Arabic poems based on a research theory called applied criticism. He introduces this criticism as one of the types of practical criticism based on the effect on the reader. His book was published in 2017. The author has collected the contents of the book in three chapters. First, the theoretical framework of the discussion, then Saadi's life and works, and at the end, the review of Saadi's Arabic poems has been compiled on the basis of practical criticism. In this article, an effort is made to describe, analyze and criticize the mentioned book in the four axes of research structure, Saadiology, documentation of information and in-text references, errors, and content deficiencies. The insufficient and disorganized research method, the author's incorrect research theory, and the author's disregard for the principle of reference in the research have distracted the author from compiling a scientific and academic book that will resemble Saadi's Arabic poetry for the audience.